Flexible micro manufacturing platform for the fabrication of PMMA microfluidic devices. (October 2018) - Trotta, G.; Volpe, A.; Ancona, A.; Fassi, I.
Abstract: In this work we present a micro manufacturing platform for the production of polymeric microfluidic devices on a mass scale, based on the integration of microinjection moulding and femtosecond laser (fs-laser) micromachining technologies. A mould prototype was designed for the fabrication of polymeric thin plates characterized by simplified microfeatures representative of typical Lab-on-a-Chip (LoC) devices. The injection moulding master tool includes replaceable metallic inserts, which were fabricated by exploiting the extreme flexibility and accuracy of fs-laser milling. Here, the laser process parameters have been studied and properly adjusted to meet the target geometry and surface quality of the mould inserts, which were subsequently characterized by confocal and SEM microscopy. The micro injection moulding (μIM) process parameters for the device production have been defined by complete three-dimensional filling and packing process simulations. Finally, the micro-injection mould with reconfigurable inserts was employed for the production of thin plates with simplified microfeatures using PMMA. The ability to reproduce these microfeatures via μIM is an essential step to approach to the mass-production of a polymeric LoC and the use of replaceable micro-inserts fabricated by direct fs-laser ablation promises high flexibility in the design and manufacturing of such devices.